Review of the waspfish genus Liocranium (Scorpaeniformes: Tetrarogidae), with restoration of L. pleurostigma (Weber) - Motomura, Hiroyuki; Last, Peter R.; Johnson, Jeffrey W. (Zootaxa, 2008)
A taxonomic review of the waspfish genus Liocranium Ogilby, 1903 (Tetrarogidae) resulted in two species of the genus being regarded as valid: L. praepositum Ogilby, 1903 (type species of the genus) and L. pleurostigma (Weber, 1913) (previously regarded as a junior synonym of L. praepositum). Liocranium pleurostigma is distinguished from L. praepositum by colour pattern, gill-raker counts and several morphometrics, including upper-jaw length, depth of the posterior margin of the maxilla, length of the longest anal-fin soft ray, and position of the spine tip of the depressed pelvic fin. Lectotypes of the two nominal species are herein designated. Liocranium pleurostigma is distributed off the northwestern coast of Australia (east to Torres Strait), New Guinea and the Philippines, whereas L. praepositum occurs off the northeastern coast of Australia (north to about Hinchinbrook Island). Comments on the biogeography of Liocranium are also provided.